Subjective Darkness: Depression as a Disintegration of Meaning in the Core Narrative - Friedson, Meredith (Narrative Works)

(untitled) (The University of New Brunswick, 2013)
In this paper, depression is described as a disintegration of meaning within the context of attempting to narrate one’s life. The difficulties of autobiographical narrative are explored, as are the shortcomings of language in conveying existential pain. A common societal response to attempts at narrative is to turn away, to silence the individual, and this leads to further difficulties in mourning and recovery. Clinical cases are used to elucidate the characteristics of depressive experience and the importance of narrative in the healing process. In addition, ethical issues regarding qualitative narrative research are discussed.